Design and development of an early warning system to prevent the effects of debris flow in la Quebrada Pedregal, Chosica - Lima - Gutiérrez Lavini, Giusepi Joel (2021)
Chosica is an area with special characteristics that cause debris flows, the geology is composed of the Santa Rosa superunit of the Upper Cretaceous, composed of Tonalitic and Granodioritic outcrops, which are covered by alluvial deposits belonging to the Quaternary of the Pleistocene series and Holocene, the main geoforms are streams and alluvial terraces composed of various debris flows. In the present work, an early warning system was designed and developed through a mobile application (App) to prevent the residents of the Pedregal stream from the effects generated by the huaicos through an early warning system based on rainfall sensors. They measure the amount of precipitation that has fallen in a place during a given time and accelerometers that can measure the degree of acceleration or movement. The application consists of a series of interfaces, the main three being the Welcome, the second the Map where you can see the location of the user and the sensors and the Prevention Culture interface, where the user can find educational alternatives on the huaico, how to act before it and the alert system. This application could be used in other types of mass movement phenomena.